Pushed out contested development and rural gentrification in the US West - Ryanne Pilgeram (Seattle University of Washington Press, 2021)
What happens to rural communities when their traditional economic base collapses? When new money comes in, who gets left behind? Pushed Out offers a rich portrait of Dover, Idaho, whose transformation from "thriving timber mill town" to "economically depressed small town" to "trendy second-home location" over the past four decades embodies the story and challenges of many other rural communities. Sociologist Ryanne Pilgeram explores the structural forces driving rural gentrification and examines how social and environmental inequality are written onto these landscapes. Based on in-depth interviews and archival data, she grounds this highly readable ethnography in a long view of the region that takes account of geological history, settler colonialism, and histories of power and exploitation within capitalism. Pilgeram's analysis reveals the processes and mechanisms that make such communities vulnerable to gentrification and points the way to a radical justice that prioritizes the economic, social, and environmental sustainability necessary to restore these communities
Includes bibliographical references and index.
Keywords: Gentrification--Idaho--Dover. | Dover (Idaho)--Economic conditions. | Dover (Idaho)--Social conditions